Genotype distributions in top-level soccer players: A role for ACE? - Juffer, P.; Furrer, R.; Gonzalez-Freire, M.; Santiago, C.; Verde, Z.; Serratosa, L.; Morate, F. J.; Rubio, J. C.; Martin, M. A.; Ruiz, J. R.; Arenas, J.; Gomez-Gallego, F.; et al. (International Journal of Sports Medicine, 2009)
We determined the genotype and allelic frequency of several genetic polymorphisms (ACE I/D, GDF-8 K153R [and also E164 K, P198A and I225 T] and AMPD1 C34 T) that are candidates to influence sports performance in a group of 54 male professional soccer players. Their results were compared with those of elite endurance male athletes (52 runners) and 123 sedentary, healthy men (controls). We found statistical significance for the ACE ID ( 2(2)=8.176, P=0.017) and II genotypes ( 2(2)=16.137, P<0.001) with a higher and lower frequency of ID (P=0.005) and II (P<0.001), respectively, in soccer players than in endurance runners. Statistical significance was also reached for AMPD1 (with a higher frequency of the CT genotype in soccer players than in runners [ 2(2)=7.538, P=0.006]) but not for GDF-8 K153R. Since the ACE II genotype is associated with improved potential for endurance performance but with decreased training gains in muscle mass and strength, these findings together with previous results [37] support the notion that elite soccer players tend to have a power/strength oriented genotype.